Fishery Technology Developments: Transforming the Aquatic Sector - Parvez O; Siddharth E (Advances in Aquaculture and Fisheries Management, 2024)
This essay looks at how fishing technology advancements have revolutionized the aquatic industry. In a world where sustainable fishing practices and responsible resource management are vital, innovative technologies have emerged as indispensable tools. Precision fishing equipment, fish identification and tracking, aquaculture automation, sustainable fishing practices, drones and aquatic robots, and sustainable fishing applications are some examples of these technologies. These developments have led to improved resource management, increased fishing sector efficiency, and a new era of sustainable fishing. In order to address problems like overfishing, illegal fishing, and environmental sustainability, they are crucial. As the demand for seafood increases globally, adoption and investment in these technologies are critical to a healthy future for aquatic life and the livelihoods of those who depend on it.